1990
DOI: 10.1086/261716
|View full text |Cite
|
Sign up to set email alerts
|

Unobservables, Pregnancy Resolutions, and Birth Weight Production Functions in New York City

Abstract: This paper makes contributions to the estimation of health production functions and the economics of fertility control. We present the first infant health production functions that simultaneously control for selfselection in the resolution of pregnancies as live births or induced abortions and in the use of prenatal medical care services. We also incorporate the decision of a pregnant woman to give birth or obtain an abortion into economic models of fertility control and use information conveyed by this decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(157 citation statements)
references
References 16 publications
9
146
1
1
Order By: Relevance
“…If each of these fatalities led to a 0.0032 increase in the probability of being in the low-birth-weight category, then roughly 241 of the estimated 786 children born in November to mothers living in Nablus were pushed below the 2,500 gram cuto¤ as a result of being exposed to armed con ‡ict during their …rst trimester in the womb. 26 Of course the …ghting was at its most intense in Nablus during these months, while other districts were calmer. Tulkarm were pushed below the 2,500 gram cuto¤ as a result of being exposed to violence during the …rst trimester.…”
Section: Robustness Checksmentioning
confidence: 96%
“…If each of these fatalities led to a 0.0032 increase in the probability of being in the low-birth-weight category, then roughly 241 of the estimated 786 children born in November to mothers living in Nablus were pushed below the 2,500 gram cuto¤ as a result of being exposed to armed con ‡ict during their …rst trimester in the womb. 26 Of course the …ghting was at its most intense in Nablus during these months, while other districts were calmer. Tulkarm were pushed below the 2,500 gram cuto¤ as a result of being exposed to violence during the …rst trimester.…”
Section: Robustness Checksmentioning
confidence: 96%
“…Douglas Almond and Janet Currie (2011) argue that these investments have large and lifelong effects on children's well-being as adults. Moreover, a number of studies have shown that the availability of abortion improves infant outcomes by reducing the number of low-birthweight babies (Grossman and Jacobowitz 1981, Joyce 1987, Grossman and Joyce 1990. Using a specification identical to the one described above, table 2 examines whether the faster diffusion of the Pill in certain states affected the share of infants with low birthweights.…”
Section: B the Effects Of Increasing Legal Access To The Pill Onmentioning
confidence: 99%
“…Studies examining the determinants of birth weights or fetal and neonatal mortality therefore typically focus on whether care is provided in the first trimester, or on the number of months from the beginning of pregnancy until prenatal care is first received (e.g. Rosenzweig and Schultz, 1983;Grossman and Joyce, 1990;Frank et. al., 1992;or Warner, 1995). infrastructure and most lifestyle choices are unlikely to be affected by parental leave entitlements but may be correlated with them, and so need to be controlled for in the analysis.…”
mentioning
confidence: 99%